Analysis of Factors Related to Performance of Midwife in Antenatal Care Services at the Community Health Center of Jayawijaya Regency - Ance Tatogo, Sukri Palutturi, Darmawansyah, Amran Razak, Yahya Thamrin, Muh Asdar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to determine the factors that influence the performance of midwives in antenatal care services in Jayawijaya Regency. The study used observational research with a cross sectional study design. The population consisted of all midwives at the Hom-Hom, Elekma, Walelagama, Asolokobal, Kurulu and Asologaima health centers. Data were obtained using a questionnaire and analyzed using chi square and binary logistic regression. The results showed that there was a relationship between age and the performance of midwives in ANC services with p-value = 0.046, there was a relationship between the status of midwives in ANC services and the performance of midwives with p-value = 0.018, there was a relationship between years of service and performance of midwives in ANC services. with p-value = 0.004, there is no relationship between knowledge and performance of midwives in ANC services with p-value = 0.479, there is a relationship between attitudes towards midwives' performance in ANC services with p-value = 0.001, there is a relationship between motivation and performance midwives in ANC services with a p-value = 0.011, there is no relationship between the leadership of the head of the puskesmas (Community Health Center) on the performance of midwives in ANC services with a p-value = 1,000, and there is a relationship between facilities and the performance of midwives in ANC services with a p-value = 0.008. Suggestions for the health office to evaluate the puskesmas facilities, and for midwives to carry out ANC services in accordance with a full sense of responsibility.